Химическое осаждение из газовой фази гетеро- и наноструктур соединений III–V - Voronin, V. A.; Guba, S. K.; Kurilo, I. V. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The results of a phenomenological study based on the in-situ method of UV spectroscopy of the gas-phase composition in the source regions of GaAs, GaP, In, Ga, and In/Ga in a horizontal flow reactor are described. The experimental results are used to analyze the growth process of GaAs:Bi, GaAs1–хPх, In1–хGaхAs, InхGa1–хAsуP1–у layers by a low-temperature isothermal gas-transport chloride epitaxy method. The obtained data make it possible to determine the temperature and the range of carrier gas (H₂) flow rates required to form a supersaturated gas phase during low-temperature growth of hetero- and nanostructures based on GaAs, GaAs1–хPх, In1–хGaхAs, InхGa1–хAsуP1–у layers.